Assessing ethical competence: the case of human resource management in South Africa - Felgate, Yendor Reginald (My University, 2018)
The role of Human Resources Management (HRM) can be characterised as “provid[ing] direction as to how an organisation should handle people so that organisation[al] effectiveness and individual satisfaction are maximised” (Trezise, 1996:87). Such a role inevitably creates a number of ethical tensions. If HRM practitioners face difficult ethical challenges in organisations, then it follows that it is important to understand what type of ethical expertise they require to address these challenges. My first aim will be to assess whether prevailing models of ethical expertise are able to conceptualise moral agency and the capacity that is needed to develop such agency in HRM. In this regard, I shall argue that the prevailing models are insufficient for their purposes. My second aim will be to develop a more satisfactory account. I will argue that a broader notion of ethical expertise is required: one, which includes not only virtue but also the process of deliberation and the application of moral agency; which is effectively able to deal with a multitude of situations; and which has a chance of identifying the best alternatives in complex HRM ethical situations. Such an expanded notion of ethical expertise potentially strengthens the ability of HRM practitioners to be more effective as ethical stewards.
An Applied Ethics for Professionals Research Report Submitted to the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Art, 2018
Keywords: Personnel management--Moral and ethical aspects--South Africa; Employees--Recruiting--South Africa